Therapy for Stage IV Non–Small-Cell Lung Cancer Without Driver Alterations: ASCO Living Guideline. Issue 28 (1st October 2022) - Singh, Navneet; Temin, Sarah; Baker, Sherman; Blanchard, Elizabeth; Brahmer, Julie R.; Celano, Paul; Duma, Narjust; Ellis, Peter M.; Elkins, Ivy B.; Haddad, Rami Y.; Hesketh, Paul J.; Jain, Dharamvir; et al.
Abstract : Living guidelines are routinely updated guidelines that are developed for selected topic areas with rapidly evolving evidence that drives frequent change in clinical practice. These guidelines are updated on a regular schedule, based on the work of a standing panel that reviews the literature on a continuous basis. Updates will be made regularly and can be found at https://ascopubs.org/nsclc-non-da-living-guideline . PURPOSE: To provide evidence-based recommendations updating the 2020 ASCO and Ontario Health (Cancer Care Ontario) guideline on systemic therapy for patients with stage IV non–small-cell lung cancer without driver alterations. METHODS: ASCO updated recommendations on the basis of an ongoing systematic review of randomized clinical trials from 2018 to 2021. RESULTS: This guideline update reflects changes in evidence since the previous update. Five randomized clinical trials provide the evidence base. Outcomes of interest include efficacy and safety. RECOMMENDATIONS: In addition to 2020 options for patients with high programmed death ligand-1 (PD-L1) expression (tumor proportion score [TPS] ≥ 50%), nonsquamous cell carcinoma (non-SCC), and performance status (PS) 0-1, clinicians may offer single-agent atezolizumab. With high PD-L1 expression (TPS ≥ 50%), non-SCC, and PS 0-1, clinicians may offer nivolumab and ipilumumab alone or nivolumab and ipilimumab plus chemotherapy. With negative (0%) and low positive PD-L1 expression (TPS 1%-49%), non-SCC, and PS 0-1, clinicians may offer nivolumab and ipilimumab alone or nivolumab and ipilimumab plus chemotherapy. With high PD-L1 expression, SCC, and PS 0-1, clinicians may offer single-agent atezolizumab. With high PD-L1 expression, squamous cell carcinoma (SCC), and PS 0-1, clinicians may offer nivolumab and ipilimumab alone or in combination with two cycles of platinum-based chemotherapy. With negative and low positive PD-L1 expression, SCC, and PS 0-1, clinicians may offer nivolumab and ipilimumab alone or in combination with two cycles of platinum-based chemotherapy. With non-SCC who received an immune checkpoint inhibitor and chemotherapy as first-line therapy, clinicians may offer second-line paclitaxel plus bevacizumab. With non-SCC, who received chemotherapy with or without bevacizumab and immune checkpoint inhibitor therapy, clinicians should offer the options of third-line single-agent pemetrexed, docetaxel, or paclitaxel plus bevacizumab. Additional information is available at www.asco.org/thoracic-cancer-guidelines .